East Asian dust storm in May 2017: observations, modelling, and its influence on the Asia-Pacific region - X.-X. Zhang (Atmospheric Chemistry and Physics, 2018)
A severe dust storm event originated from the Gobi Desert in Central and East Asia during 2–7 May 2017. Based on Moderate Resolution Imaging Spectroradiometer (MODIS) satellite products, hourly environmental monitoring measurements from Chinese cities and East Asian meteorological observation stations, and numerical simulations, we analysed the spatial and temporal characteristics of this dust event as well as its associated impact on the Asia-Pacific region. The maximum observed hourly PM10 (particulate matter with an aerodynamic diameter  ≤  10 µm) concentration was above 1000 µg m−3 in Beijing, Tianjin, Shijiazhuang, Baoding, and Langfang and above 2000 µg m−3 in Erdos, Hohhot, Baotou, and Alxa in northern China. This dust event affected over 8.35 million km2, or 87 % of the Chinese mainland, and significantly deteriorated air quality in 316 cities of the 367 cities examined across China. The maximum surface wind speed during the dust storm was 23–24 m s−1 in the Mongolian Gobi Desert and 20–22 m s−1 in central Inner Mongolia, indicating the potential source regions of this dust event. Lidar-derived vertical dust profiles in Beijing, Seoul, and Tokyo indicated dust aerosols were uplifted to an altitude of 1.5–3.5 km, whereas simulations by the Weather Research and Forecasting with Chemistry (WRF-Chem) model indicated 20.4 and 5.3 Tg of aeolian dust being deposited respectively across continental Asia and the North Pacific Ocean. According to forward trajectory analysis by the FLEXible PARTicle dispersion (FLEXPART) model, the East Asian dust plume moved across the North Pacific within a week. Dust concentrations decreased from the East Asian continent across the Pacific Ocean from a magnitude of 103 to 10−5 µg m−3, while dust deposition intensity ranged from 104 to 10−1 mg m−2. This dust event was unusual due to its impact on continental China, the Korean Peninsula, Japan, and the North Pacific Ocean. Asian dust storms such as those observed in early May 2017 may lead to wider climate forcing on a global scale.